ANALISIS PENGARUH EFISIENSI MODAL KERJA TERHADAP PROFITABILITAS PADA PT. KRAKATAU STEEL, TBK - Afandi Afandi; Iroh Rahmawati (FKIP, Universitas Banten Jaya, 2020)
This study aims to find out how the Efficiency Analysis of Working Capital Against Profitability at PT. Krakatau Steel,Tbk.This study uses a quantirative method. The population in this study is te overall financial statements of PT. Krakatau Steel, Tbk in the year (2014-2017), while the sample in this study is the balance sheet and income statement for the year (2014-2017). The technique of data collection is done by documentation and library techniques. The data analysis technique used is simple linear regression. The results of this study indicate that working capital has no significant effect on profitability at PT. Krakatau Steel, Tbk.